2008
DOI: 10.1071/rd07147
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and anti-oxidant defences in swine follicular fluids

Abstract: A growing body of evidence indicates that the pro-oxidant/anti-oxidant balance inside the ovarian follicle plays an important role in folliculogenesis. Therefore, the aim of the present study was to assess the redox status of follicular fluids collected from different-sized swine follicles. We quantified the most important reactive oxygen species (ROS), namely superoxide anion (O(2)(-)), hydrogen peroxide and hydroperoxides (ROOH); in addition, we examined the activity of the detoxifying enzymes superoxide dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 18 publications
5
47
2
2
Order By: Relevance
“…1) arresting nuclear maturation in vitro allowing optimal capacitation of cytoplasm, 2) growing oocytes inside the follicle, and 3) identification of biomarkers of oocyte competence in granulosa and cumulus cells and metabolites in the FF (32). The study of Basini et al in 2016 was different with our study in type of sample but was similar to in rreactive oxygen and anti-oxidant defenses in FFs (33).…”
Section: Discussioncontrasting
confidence: 76%
“…1) arresting nuclear maturation in vitro allowing optimal capacitation of cytoplasm, 2) growing oocytes inside the follicle, and 3) identification of biomarkers of oocyte competence in granulosa and cumulus cells and metabolites in the FF (32). The study of Basini et al in 2016 was different with our study in type of sample but was similar to in rreactive oxygen and anti-oxidant defenses in FFs (33).…”
Section: Discussioncontrasting
confidence: 76%
“…The Cu-Zn SOD and Mn SOD are important primary intracellular ROS scavenger enzymes [Yu, 1994;Matos et al, 2009] and their activities have been reported in preantral, antral, and dominant follicles [Laloraya et al, 1989[Laloraya et al, , 1998Suzuki et al, 1999;Fujii et al, 2005;Matos et al, 2009]. The higher levels of ROS have been reported in the follicular fluids of Swine and Cow [Basini et al, 2008;Rizzo et al, 2009].…”
Section: Follicular Production Of Rosmentioning
confidence: 99%
“…Although O 2 concentration in the oviduct of mammals varies between 2% and 9% [11], several culture systems [12][13][14] find success culturing at atmospheric condition (20%). However, this supraphysiological concentration has been associated with increased concentrations of reactive oxygen species, which alters the culture environment, thus hindering embryo development [15,16]. However, some laboratories find increased development when embryos are cultured in 20% O 2 and FBS augments blastocyst rates [17].…”
Section: Introductionmentioning
confidence: 99%